Resource co-allocation framework based on hybrid gaming model in grid environments. (1st January 2013) - Xiao, Peng; Liu, Dongbo; Qu, Xilong
Resource co-allocation is a fundamental infrastructure to aggregate heterogeneous and distributed resources in grid environments. Although it has been widely investigated, co-allocation under multiple QoS constraints still remains an open issue. To address the issue of resource co-allocation with constraints to budget and deadline, a game-based co-allocation framework is proposed. This framework optimises resources deployment and prices scheme by a three-side co-allocation mechanism; meanwhile, it provides quantitative deadline guarantees for applications by applying queuing system to model the working of grid resources. The validity and solutions of the framework are presented theoretically. Experimental results show that the proposed framework can significantly reduce the deadline missing rate and resource costs for those applications with constraints to cost and deadline.